An Investigation and Development of Communication Skills Training for Children with Intellectual Disabilities - Asma Ishtiaq,; Dr. Shamaiela Farooqi,; Dr. Shafqat Rasool , (Dialogue Social Science Review (DSSR), 2025)
This research focused on the development and evaluation of a communication skills training program for children with intellectual disabilities (ID). The objectives of this study included: (1) developing ecological inventories for assessing communication skills, (2) assessing the communication skills of children with ID, (3) creating a communication training program, (4) evaluating the program’s effectiveness, and (5) providing recommendations for improving communication skills in these children. Ten boys with ID from Faisalabad were selected for the development of ecological inventories and training programs. Tasks for the program were designed using task analysis principles and behavior modification techniques to enhance communication skills. Findings indicated that the program effectively improved communication skills through behavior modification. This research provides valuable insights and practical guidelines for improving communication strategies in special education settings.